Substance use disorder patients' expectations on transition from treatment to post-discharge period. Issue 3 (June 2020) - Johannessen, Dagny Adriaenssen; Nordfjærn, Trond; Geirdal, Amy Østertun
Aim: There is limited knowledge about how inpatients anticipate factors that facilitate the transition between specialised inpatient treatment for substance use disorder (SUD) and the post-discharge period. This study explores factors that inpatients anticipated would facilitate such a transition period. Method: A focus group study, consisting of four group interviews with individuals in inpatient SUD treatment, was conducted to explore their expectations for the transition and post-discharge period ahead of them. The transcribed interview material was analysed using thematic analysis. Findings: The analytical process led to three themes: "Belonging", "Intrapersonal processes" and "Predictability". Correspondence between inpatients' expectations and the services they are offered in the transition and post-discharge period may serve as proper support for inpatients ahead of a vulnerable phase, such as the transition and post-discharge period. Conclusions: Findings from the current study highlight overarching elements that inpatients envisioned to be facilitating, such as social support, motivation, self-efficacy, self-awareness and predictability in basic elements such as employment, housing and personal finances. Findings from this study and previous ones imply that certain factors appear to facilitate in vulnerable phases, such as service level transitions. These facilitating factors should be taken into consideration and used as steppingstones through the transition and post-discharge period after inpatient SUD treatment.